Lokakarya Kreatif Pembuatan Sabun Berbahan Alami sebagai Upaya Pemberdayaan Guru SD Labschool Unesa 1 dalam Mendukung Sekolah Berkelanjutan - Evi Farsiah Utami; Fenty Fahminnasih; Setya Putri Erdiana (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Teachers play a crucial role in fostering environmental awareness among students. Therefore, capacity building through practical and sustainable activities is essential. This community service project aims to empower teachers at SD Labschool Unesa 1 through a creative workshop on making natural soap to support sustainable schools. The activity employed a participatory approach, including environmental product education, demonstrations, hands-on practice, and discussions. Results showed that all participants were able to produce soap independently, with 90% demonstrating increased understanding of the benefits of natural ingredients as eco-friendly cleaning alternatives. Participants also expressed enthusiasm for applying the training outcomes in their teaching and school programs. This workshop proved that practice-based training effectively enhances teachers’ competencies and supports the implementation of environmental education for sustainable schools.